2021
DOI: 10.1016/j.jcf.2021.08.035
|View full text |Cite
|
Sign up to set email alerts
|

Remote monitoring in telehealth care delivery across the U.S. cystic fibrosis care network

Abstract: Background: Cystic fibrosis (CF) programs and people with CF (PwCF) employed various monitoring methods for virtual care during the COVID-19 pandemic. This paper characterizes experiences with remote monitoring across the U.S. CF community. Methods: The CF Foundation (CFF) sponsored distribution of home spirometers (April 2020 to May 2021), surveys to PwCF and CF programs (July to September 2020), and a second program survey (April to May 2021). We used mixed methods to explore access, use, and perspectives re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 28 publications
0
22
0
Order By: Relevance
“…Since the onset of the pandemic PwCF/families have played a more active role in taking measurements at home (e.g. height, weight, blood glucose, homespirometry) and coordinating collection of blood and respiratory samples, collected at home (and mailed to the care center for anal-ysis) or collected and analyzed at other locations (with the results sent to the care center) [24] . The COVID-19 pandemic has empowered more patients to take a larger stake in tracking their health care metrics.…”
Section: Recognizing the Changing Role Of People With Cf And Familiesmentioning
confidence: 99%
“…Since the onset of the pandemic PwCF/families have played a more active role in taking measurements at home (e.g. height, weight, blood glucose, homespirometry) and coordinating collection of blood and respiratory samples, collected at home (and mailed to the care center for anal-ysis) or collected and analyzed at other locations (with the results sent to the care center) [24] . The COVID-19 pandemic has empowered more patients to take a larger stake in tracking their health care metrics.…”
Section: Recognizing the Changing Role Of People With Cf And Familiesmentioning
confidence: 99%
“…During the COVID‐19 pandemic, there was a rapid shift to telehealth services to maintain access to ambulatory care 2 . PwCF were eager for solutions to the limited in‐person assessments 3 and there was widespread adoption of home spirometry in the CF population in the United States 4 and globally 5 . Prior validation studies of various devices demonstrated concordance to in‐clinic measures in a supervised setting, 6,7 with conflicting findings of accuracy in an unsupervised setting 8–10 .…”
Section: Introductionmentioning
confidence: 99%
“…In general, this has been reasonably successfully implemented and accepted by PwCF and care providers, particularly adults [8] , [9] , [10] , [11] , [12] . Health care providers and PwCF have adapted to home spirometry, remote microbiological sample collection, blood monitoring and video consultants well [ 7 , 10 , 13 ]. Advantages include less risk of cross infection and convenience for PwCF who are clinically well [ 10 , 14 , 15 ].…”
Section: Impact Of Covid-19 On Clinical Carementioning
confidence: 99%
“…Disparities in high speed internet access and technology may create a ‘digital divide' [ 9 , 12 , 17 ]. Whilst the surge in telehealth has subsided and confidence in returning to face to face visits has grown, in person consultations will probably not return to pre pandemic levels [ 6 , [10] , [11] , [12] , [13] , [14] ]. Health care delivery has evolved and there is much work to do with evaluation and implementation of new hybrid models that address the individual needs of PwCF.…”
Section: Impact Of Covid-19 On Clinical Carementioning
confidence: 99%